Endoscopic submucosal dissection of gastric lesions by using a master and slave transluminal endoscopic robot: an animal survival study - Wang, Z.; Phee, S. J.; Lomanto, D.; Goel, R.; Rebala, P.; Sun, Z. L.; Trasti, S.; Reddy, N.; Wong, J. Y. Y.; Ho, K. Y. (Endoscopy, 2012)
Background and study aims: The feasibility of performing endoscopic submucosal dissection (ESD) using the Master and Slave Transluminal Endoscopic Robot (MASTER), a robotics-enhanced surgical system, has been shown in our previous study. This study aimed to further explore, in an animal survival study, the 2-week outcome of using MASTER to perform ESD.Patients and methods: In this prospective study, ESD was performed on five female pigs (weighing 32.4 – 36.8 kg) under general anesthesia using the MASTER. The animals were observed for 2 weeks before being humanely killed for necropsy examination. The main outcome measures were completeness of resection, procedure-related complications, and survival at 2 weeks.Results: The procedure was successfully completed in all five pigs. It took a mean of 21.8 minutes (range 6 – 39 minutes) to complete the ESD of each gastric lesion. All lesions were excised en bloc; the average dimension of the lesions was 77 mm (range 25 – 104 mm). One pig sustained a small intraoperative perforation which was identified and successfully clipped. After completion of the ESD procedures, all pigs survived well for 2 weeks. Necropsy was performed, with intraoperative gastroscopy identifying all the ESD sites as healed. Histopathologic examination showed all ESD sites had healed with partial epithelialization. Microbiological tests of the peritoneal fluid showed only microbes typically found in pigs.Conclusion: Performing ESD with MASTER was feasible and safe in this 2-week animal survival study.